The Influence Of Personality And FinancialLiteracy Towards Investment Decision Among Student In Faculty Of Economy And BusinessUniversity Of Sam Ratulangi - Pieta S. Pitoy (Jurnal Riset Multidisiplin Edukasi, 2025)
This study explores the influence of Personality and Financial Literacy on Investment Decisions among students of the Faculty of Economics and Business, Sam Ratulangi University. The increasing number of investors in the Indonesian capital market, especially among the younger generation, requires a deeper understanding of the factors that drive investment behavior. In mid-2022, data from KSEI showed a significant increase in stock investors, with 81.64% of investors under the age of 40, especially from Generation Z and Millennials. This demographic trend indicates a strong interest in investment opportunities even though many individuals do not yet have a stable income. This study used a quantitative methodology, using a structured questionnaire to collect data from students. The findings of this study indicate that Personality and Financial Literacy significantly influence Investment Decisions. This study concludes that improving financial literacy programs and personality development workshops can significantly improve students' ability to make good investment decisions. This study contributes to the understanding of how personality traits and financial knowledge influence investment behavior especially among young adults, providing valuable insights for students, educators and policymakers who aim to promote financial literacy.